Full of myself : Black womanhood and the journey to self-possession - Brown, Austin Channing (Convergent, 2025)
"As an antiracism educator and writer leading through America's cycles of racial unrest, Austin Channing Brown reached a crossroads. "I love my work," she writes, "and I am tired. We are tired. Tired of protesting. Tired of 'saving democracy.' Tired of educating and explaining." She began to ask, "What do I deserve, not just as a citizen but as a human?" Full of Myself is her answer to that question. Weaving personal narrative with perceptive social commentary, she offers a look at the mechanisms that limit who Black women are allowed to be-at work, at home, in community-and the defining moments when she decided self-possession is the justice work she had been made to undervalue. From skinny dipping in the ocean to becoming a mom, she delves into the drama of life and invites readers to begin defining themselves not as empty vessels to improve the world, but as a people born free in spirit, in hope, in joy. For Black women seeking to understand the true roots of their burnout, or anyone wondering what it means to live joyfully in a hostile world, Full of Myself is a breath of fresh air and an invitation to full humanity."-- Provided by publisher.